Global homeomorphism of nonsmooth mappings using pseudo-Jacobian on Riemannian manifolds - Ghahraei, E. (Rendiconti del Circolo matematico di Palermo, 2020)
We study the global homeomorphism of a continuous nonsmooth mappings between Riemannian manifolds which may be non-locally Lipschitz. To this end, we use the notion of pseudo-Jacobian map associated to f : M → N where M and N are Riemannian manifolds and we consider a related index of regularity for f . We obtain a characterization of global homeomorphisms in terms of its index of regularity.